How Prediction Errors Shape Perception, Attention, and Motivation - Den Ouden, Hanneke E.; Kok, Peter; De Lange, Floris P. (Frontiers in Psychology, 2012)
Prediction errors are a central notion in theoretical models of reinforcement learning, perceptual inference, decision-making and cognition, and prediction error signals have been reported across a wide range of brain regions and experimental paradigms. Here, we will make an attempt to see the forest for the trees, considering the commonalities and differences of reported prediction errors signals in light of recent suggestions that the computation of prediction errors forms a fundamental mode of brain function. We discuss where different types of prediction errors are encoded, how they are generated, and the different functional roles they fulfil. We suggest that while encoding of prediction errors is a common computation across brain regions, the content and function of these error signals can be very different, and are determined by the afferent and efferent connections within the neural circuitry in which they arise.